Staphylococcus aureus Myocarditis with Associated Left Ventricular Apical Thrombus - Michael McGee; Emily Shiel; Stephen Brienesse; Stuart Murch; Robert Pickles; James Leitch (Case Reports in Cardiology)
Staphylococcus aureus myocarditis is a rare diagnosis with a high mortality rate, usually seen in people who are immunocompromised. Here, we report a case of a 44-year-old man on methotrexate for rheumatoid arthritis who presented in septic shock and was diagnosed with staphylococcus aureus myocarditis. The myocarditis was associated with a left ventricular apical thrombus, with normal systolic function. The myocarditis and associated thrombus were characterised on transthoracic echocardiogram and subsequently on cardiac magnetic resonance imaging. Cardiac magnetic resonance (CMR) imaging showed oedema in the endomyocardium, consistent with acute myocarditis, associated with an apical mural thrombus. Repeat CMR 3 weeks following discharge from hospital showed marked improvement in endomyocardial oedema and complete resolution of the apical mural thrombus. He was treated with a 12-week course of antibiotics and anticoagulated with apixaban. The patient was successfully managed with intravenous antibiotics and anticoagulation with complete recovery.